(untitled) (American Journal of Islam and Society, 1988)
As the ideas of struggle against imperialism and class were prominent among social scientists a generation ago, those of ethnicity are in the forefront today. Ethnicity-language, race, folk culture, food, etc., cut across class and sect. In Africa and Asia it has assumed violent political shape, succeeding in creating nations like Bangladesh or seriously disrupting them as in the case of (Sri Lanka). The interrelationship of ethnicity with the state and religion are explored in Pakistan, Iran and Afghanistan in the book. It is the very fuzziness of these central concepts - state, religion, ethnicity - that creates so much heat around their discussion. The theoretical linkages between the concepts in these three states are clear. Not so clear is the method to resolve tensions between them. A book, then, which brings together “an outstanding group of anthropologists, historians, political scientists and Islamicists” promises value. Fourteen distinguished academics have combined to produce the contents of the book. Some cannot resist the pitfall into which social scientists are wont to plummet, i.e., the use of impenetrably recondite jargon: “Whatever the particular criterion for group identity, inquiry into the relationship of ethnic groups to the larger sociocultural systems of which they are a part ought to rest on the ‘situational’ approach to ethnicity” (P. Higgins: p.169). Mercifully this kind of language is restricted. African and Asian scholars will be quick to apply the label “Orientalist” to some of the participants. Others will note that the 4 authors of the chapters on Pakistan are non-Muslims; an observation not entirely irrelevant about a book on ethnicity and religion. This kind of emotionalism however, must not be allowed to distract from the quality of the work. The papers are scholarly, and most are based on a life-time’s work. They attempt to discuss the central issues in complex and changing societies. The editors, in a comprehensive and useful introduction, lay out their ...